2017
DOI: 10.3758/s13423-017-1319-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Unexpected events disrupt visuomotor working memory and increase guessing

Abstract: Data Files: Raw data and analysis scripts are at OSF URL https://osf.io/g9pvd/ Acknowledgements: The authors thank Fabrice Parmentier and Sirawaj Itthiipuripat for helpful advice on task design, and Francesco Marini for programming. This research was funded by a grant from NIH (R21 NS085543), and the James S McDonnell (#220020375). 2 AbstractWhen a unexpected event, such as a car honking, occurs in daily life, it often disrupts our train of thought. In the lab, this effect was recently modeled with a task in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Behavioral and electrophysiological studies have shown that deviance distraction originates from the violation of sensory predictions rather than from the deviant sound’s low probability per se [ 42 46 ], is associated with a transient inhibition of actions [ 47 50 ], and is unaffected by response predictability [ 51 ]. Violations of predictions can potentially also take another form, however: the omission of the predicted auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral and electrophysiological studies have shown that deviance distraction originates from the violation of sensory predictions rather than from the deviant sound’s low probability per se [ 42 46 ], is associated with a transient inhibition of actions [ 47 50 ], and is unaffected by response predictability [ 51 ]. Violations of predictions can potentially also take another form, however: the omission of the predicted auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%